1988
DOI: 10.1177/016235328801100406
|View full text |Cite
|
Sign up to set email alerts
|

Is Being Gifted a Social Handicap?

Abstract: The paper explores the question of how gifted and talented adolescents experience being gifted in high school. Fifteen subjects were interviewed twice while attending a special summer program in order to answer this general question. The data were analyzed and interpreted using a set of research questions which postulated that the subjects would voice feelings of difference and would make statements indicating recognition that being gifted interfered with full social acceptance. The results support the notion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0
8

Year Published

1989
1989
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 176 publications
(114 citation statements)
references
References 1 publication
4
102
0
8
Order By: Relevance
“…This assertion reflects tenets two and three of the SGP. Moreover, this controlling of information about oneself is considered a behavioral manifestation of social cognition-acting in accordance with social goals (Cross, Coleman & Terharr-Yonkers, 1991 & Cross, 1988;Cross, Coleman & Stewart, 1993;Cross, Coleman & Terharr-Yonkers, 1991). At this point we do not know how to explain why some gifted students manage information about themselves while others do not.…”
Section: Social Cognitive Theorymentioning
confidence: 98%
See 1 more Smart Citation
“…This assertion reflects tenets two and three of the SGP. Moreover, this controlling of information about oneself is considered a behavioral manifestation of social cognition-acting in accordance with social goals (Cross, Coleman & Terharr-Yonkers, 1991 & Cross, 1988;Cross, Coleman & Stewart, 1993;Cross, Coleman & Terharr-Yonkers, 1991). At this point we do not know how to explain why some gifted students manage information about themselves while others do not.…”
Section: Social Cognitive Theorymentioning
confidence: 98%
“…[ n addition to feeling different, some students experience giftedness in school as a social handicap (Coleman & Cross, 1988) and use coping strategies in potentially stigmatizing situations to avoid being labeled aberrant by other students (Coleman, 1985;Cross, Coleman & Stewart, 1993). For example, when faced with potentially stigmatizing situations such as exposing their ease with a test others found extremely difficult, some gifted adolescents will not tell the truth in order to reduce their social vulnerability (Cross, Coleman & TerharrYonkers, 1991).…”
mentioning
confidence: 99%
“…Klasse im unterschied zu Jüngeren eher weniger über ihr schulisches leistungsverhalten und gute Schulleistungen sprechen, um nicht in der Popularität bei Gleichaltrigen zu sinken. Auf ein negatives Verhältnis zwischen Schulleistung und Peer-Akzeptanz weisen zudem Ergebnisse von Coleman und Cross (1988) zur sozialen Stigmatisierung von hochbegabten hin. die Schulnähe oder Schulentfremdung einer Peergruppe ist als schultyp-, herkunfts-und geschlechtstypisch anzunehmen (Fend 1989).…”
Section: Schulentfremdung Und Schulerfolgunclassified
“…Gifted students have reported that the visibility of their advanced intellectual ability in some social contexts can be problematic; some believe that when others recognize their giftedness, they are perceived as different and treated as such (Coleman & Cross, 1988;Cross et al, 1993;Janos, Fung, & Robinson, 1985;Manaster, Chan, Watt, & Wiehe, 1994;Manor-Bullock, Look, & Dixon, 1995;Robinson, 1990). Some gifted adolescents, not necessarily wanting to differ from their peers in intellectual ability or be treated differently because of it, employ a variety of social coping strategies that serve to manipulate the visibility of their giftedness so that they may avoid the "perceived negative social effects of recognized high ability" (Swiatek, 2002, p. 66).…”
Section: Curry School Of Education At the University Of Virginiamentioning
confidence: 99%